IMPLEMENTATION OF SOCIAL REHABILITATION PROGRAMS FOR CHILDREN CONTACTING THE LAW IN PEKANBARU CITY IN 2019 - Pratama, Yuli Dian; Wicaksono, Baskoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 17 of 2018 concerning the organization and working procedures of the technical implementation unit for children's social rehabilitation within the directorate general of social rehabilitation. According to data from the Office of Women's Empowerment and Child Protection, the number of cases of violations of children's rights in 2019 was 130 cases. One of the social service programs for children who have problems dealing with the law is through the Social Rehabilitation Center for Children in Need of Special Protection (BRSAMPK). In implementing the government program, the central government established the Social Rehabilitation Center for Children Needing Special Protection (BRSAMPK) located in Rumbai, Khayangan street No. 160 Rumbai, Rumbai Pesisir District, Meranti Pandak Village, Pekanbaru.The purpose of this study is to analyze the problems that occur in the implementation of the social rehabilitation service program for children facing the law in Pekanbaru in 2019. This study uses the Edward III Implementation Theory. The method used is descriptive methods with qualitative research types. The types of research data are primary data and secondary data. Data collection techniques in this study were documentation and interviews. The data analysis technique used is descriptive qualitative data analysis.The results showed that the implementation of the BRSAMPK service program for ABH had not been optimal. This can be seen from the lack of good communication between ABH and insufficient resources for ABH. The inhibiting factor is the lack of supervision by caregivers of ABH, resulting in cases of children running away from the hostel. The right solution to overcome this problem is to further optimize the social rehabilitation program for ABH related to communication between ABH, infrastructure for ABH, as well as better supervision of ABH at BRSAMPK.Â Â Keywords: Implementation, Service, Social Rehabilitation Center for Children, Children in Facing Law.